Kajian Kuat Lentur Beton pada Perkerasan Kaku Jalan Tol Balikpapan-Samarinda - Rahmat Rahmat; Irna Hendriyani; Ryandi Dito Pratama (Media Ilmiah Teknik Sipil, 2017)
The Balikpapan - Samarinda toll road is one part of the trans Kalimantan toll road that arrived currently under construction. The construction of this toll road uses rigid pavement. Road construction This toll road by the East Kalimantan Provincial Public Works Department requires a minimum flexural strength of 45 kg / cm² for 28 days of concrete age. The purpose of this study is to study flexural strength concrete on the rigid pavement of the Balikpapan-Samarinda toll road based on the planning of concrete mixes at field. This study uses experimental methods in the laboratory. Credit samples are made based on concrete mix planning in the field and testing in the laboratory. The sample as many as 24 pieces for a cylinder size of 15 x 30, and 12 pieces for blocks measuring 15 x 15 x 60, which will remain at the age of 7, 14, 21 and 28 days. The results of the strong test on the cylinder is obtained at 382 kg / cm2, 27% bigger than planning, and flexural strength in the beam of 53.48 kg / cm2, 18% greater than requirements. So it can be concluded that the pavement work is rigid on the Balikpapan-Samarinda toll road Has been in accordance with the provisions stipulated by the East Kalimantan Provincial Public Works Department.